Theoretical and Practical Analysis on Borewell Rescue Device Using Inspection, Holding and Supporting Mechanism - K, Sriramireddy.; Satyanarayana, D.; Krishna, G.Sai Sreerama (The journal of contemporary issues in business and government, 2021)
Since the incidence of bore-well accidents in India is higher subsequently from 2006. Hence this paper aimed to design and investigate the bore well rescue system through inspection, holding and supportive mechanism. This paper considers three different cases of weight of children like 12kg, 15kg and 18kg based on which the device was designed. This study designs the device with the help of night vision camera with torchlight, oxygen pipe with an oxygen cylinder, vacuum pipe and suction cup. All the materials used were simple and effective and therefore it would help the rescue of child in both rural and urban areas at cheaper cost. The study conducts theoretical, experimental and ANSYS calculations to show the effectiveness of the proposed device. In this aspect, deformation, stress and strain was measured and observed that the proposed rescue device is suitable for chosen weight cases of children. Hence this method would definitely support the rescue paramedical and operation team efficiently.